The Ottoman Age of Exploration: By Giancarlo Casale (Oxford and New York: Oxford University Press, 2010. hbk. 292 pages) (American Journal of Islam and Society, 2011)
This very interesting treatise describes in detail the expansion in thesixteenth century of the Ottomans south and east, from Yemen and Eritreathrough the Indian Ocean and as far as Sumatra. Pivotal events were theOttoman conquest of Egypt in 1517, which opened up for them the routes toMecca, Medina, and points east—and their final expulsion from Yemen in 1636, depriving them of their key staging point in the area. The expansiontook on various forms: the increase of military power (mainly naval), thedevelopment of economic interests, and the strengthening of ties with localMuslim populations. At times, the direction and initiative came directlyfrom Constantinople—especially when the “Indian Ocean faction” wasable to exert its influence—but more usually from Ottoman functionariesin Egypt and Yemen, or even ambitious pirates. The main rivals in the areawere the Portuguese and their allies. However, developments elsewherebore heavily on this contest, which, at times, took on global proportions.Ottoman interests in the Indian Ocean were strengthened by their role asguarantors of the Holy Cities and the pilgrimage routes to them, as welltheir defense of Muslim merchants throughout the area. For their part, thePortuguese viewed their affairs as part of a plan that would, they hoped,lead ultimately to the conquest of Egypt and the Holy Land. The Ottomanconquest of Iraq was at least in part an attempt to outflank the Portuguese andprevent a Portuguese-Safavid alliance. Ultimately, though, the protractedconflict with Persia launched by Murad III in 1577, apparently swayedby opponents of the Indian Ocean faction, seriously drained Ottomanresources, and was likely a factor in their ultimate failure to control theIndian Ocean. At various times the Ottomans considered joining forceswith the French pirates or Dutch Protestants against the Portuguese. By theearly seventeenth century, neither the Ottomans nor the Portuguese werecontesting for dominance in the Indian Ocean; the key players there werethe English, Dutch, Safavids, and Mughals ...